Pathological laughing following pontine infarction due to basilar artery stenosis - (:unkn) unknown (My University, 2005)
Pathological laughing-(PL) is a situation defined by uncontrollable episodes of laughter without motivating stimulus or appropriate emotional expression. Pathological laughing has been described with cerebrovascular disorders, A 60-year-old man was admitted to the hospital with a right conjugated gaze paresis, left facial hemiparesis, nineth and tenth cranial nerve paresis, absent gag reflexes mild right sided hemiparesis.-Cranial MR angiography revealed giant dolichoectatic basilar artery and with severe stenosis at the mid portion of the basilar artery. Six months later he presented with pathological laughing. However, the exact mechanism of pathological laughing is unclear and disturbances in the coordination and modulatory functions of cerebellum and cerebro-pontocerebellar pathways might strongly explain the nature of this phenomenon.
Keywords: Basilar artery stenosis; Cerebro-ponto cerebellar pathways; Pathological laughing